Single cell PCR amplification of diatoms using fresh and preserved samples - Hamilton, Paul B.; Lefebvre, Keely E.; Bull, Roger D. (Frontiers in Microbiology, 2015)
Single cell Chelex® DNA extraction and nested PCR amplification were used to examine partial gene sequences from natural diatom populations for taxonomic and phylogenetic studies at and above the level of species. DNA was extracted from cells that were either fresh collected or stored in RNAlater. Extractions from Lugol’s fixation were also attempted with limited success. Three partial gene sequences (rbcL, 18S and psbA) were recovered using existing and new primers with a nested or double nested PCR approach with amplification and success rates between 70–96%. An rbcL consensus tree grouped morphologically similar specimens and was consistent across the two primary sample treatments: fresh and RNAlater. This tool will greatly enhance the number of microscopic diatom taxa (and potentially other microbes) available for barcoding and phylogenetic studies. The near-term increase in sequence data for diatoms generated via routine single cell extractions and PCR will act as a multiproxy validation of longer-term next generation genomics.